The Historiography of Madrasah Education and Social Dynamics in Minangkabau - Yanti, Herina; Iswantir, Iswantir (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This article examines the historiography of madrasah education and the social dynamics of the Minangkabau community in West Sumatra, Indonesia. Using a qualitative-historical approach, this study analyzes how madrasah, as a traditional Islamic educational institution, has undergone transformation in line with social, cultural, and epistemological changes. The findings show that the historiography of madrasah in Minangkabau represents a dialectical relationship between religious orthodoxy and the currents of modernization. The historical narratives that have developed both in traditional surau chronicles and writings of reformers such as Mahmud Yunus and HAMKA reveal a paradigm shift from theocentric education to a rational and integrative model of Islamic education. Sociologically, madrasah plays a significant role in supporting the social structure of Minangkabau, which is based on the principle of